2013
DOI: 10.3390/w5020405
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plants in a Constructed Wetland: Current and New Perspectives

Abstract: Abstract:The role of plants in the treatment of effluents by constructed wetland (CW) systems is under debate. Here, we review ways in which plants can affect CW processes and suggest two novel functions for plants in CWs. The first is salt phytoremediation by halophytes. We have strong evidence that halophytic plants can reduce wastewater salinity by accumulating salts in their tissues. Our studies have shown that Bassia indica, a halophytic annual, is capable of salt phytoremediation, accumulating sodium to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 78 publications
6
102
0
12
Order By: Relevance
“…No SAC 2 foi plantada a taboa (Typha latifolia), e no SAC 3 , o capim tifton-85 (Cynodon spp.). Quanto à remoção de demanda bioquímica de oxigênio (DBO) e de sólidos suspensos totais (SST), não se constatou diferença entre os SACs (p>0, 05), no entanto a eficiência de remoção de demanda química de oxigênio (DQO) foi diferente entre os SACs orgânica, mineralização de nutrientes e remoção de patógenos, bem como funcionam como intermediárias em processos físicos e químicos como filtração, adsorção, precipitação e sedimentação (BRIX, 1994;1997;BIAŁOWIEC;JANCZUKOWICZ;RANDERSON, 2011;SHELEF;GROSS;RACHMILEVITCH, 2013). Apesar de controvérsias, autores como Hua et al (2014) e Matos et al (2015), entre outros, têm demonstrado que a planta e seu sistema radicular também contribuem para o aumento do tempo de vida útil das unidades, pela atenuação do progressivo processo de obstrução do meio poroso.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…No SAC 2 foi plantada a taboa (Typha latifolia), e no SAC 3 , o capim tifton-85 (Cynodon spp.). Quanto à remoção de demanda bioquímica de oxigênio (DBO) e de sólidos suspensos totais (SST), não se constatou diferença entre os SACs (p>0, 05), no entanto a eficiência de remoção de demanda química de oxigênio (DQO) foi diferente entre os SACs orgânica, mineralização de nutrientes e remoção de patógenos, bem como funcionam como intermediárias em processos físicos e químicos como filtração, adsorção, precipitação e sedimentação (BRIX, 1994;1997;BIAŁOWIEC;JANCZUKOWICZ;RANDERSON, 2011;SHELEF;GROSS;RACHMILEVITCH, 2013). Apesar de controvérsias, autores como Hua et al (2014) e Matos et al (2015), entre outros, têm demonstrado que a planta e seu sistema radicular também contribuem para o aumento do tempo de vida útil das unidades, pela atenuação do progressivo processo de obstrução do meio poroso.…”
Section: Introductionunclassified
“…Isso leva ao questionamento do papel das macrófitas nesses sistemas (BRIX, 1997;MARA, 2004;SHELEF;GROSS;RACHMILEVITCH, 2013), não havendo consenso entre pesquisadores a respeito da efetiva importância das macrófitas aquáticas nos SACs. No entanto novos trabalhos, notadamente aqueles que consideram as perdas de água por evapotranspiração no sistema, têm evidenciado essa importância (BIAŁOWIEC; JANCZUKOWICZ; RANDUSON, 2011;MESQUITA et al, 2013).…”
Section: Introductionunclassified
“…from decomposition of organic pollutants can be removed by plant uptake. Therefore, as an essential component, wetland plants play an important role in both the constitution of a wetland system and enhancement of its treatment efficiency [12,14]. However, the amounts of nitrogen and phosphorus removed directly by plant uptake are relatively low, which, according to Dzakpasu et al [29], contributes less than 16% of the total removal rates.…”
Section: Function and Contribution Of Treatment Cellsmentioning
confidence: 99%
“…In order to obtain a better understanding of pollutant removal mechanisms, studies have been carried out by different workers on factors that determine the treatment efficiency of constructed wetland systems, including wetland types and combinations [5,10]; hydraulic and pollutant loads [2,11]; plant species [12][13][14]; substrates [15,16]; and their interactions [17,18], etc. The increasing trend in CW technology application coupled with stricter water quality standards requires development of better process design tools.…”
Section: Introductionmentioning
confidence: 99%
“…However, available publications on the assessment of the salt-accumulating plants, specifically focused on application in water desalination are scarce. In the limited studies available, the use of halophytic species in CWs was reported as a novel strategy to reduce salinity by Na + uptake [11]. In addition, several halophytic species have demonstrated the capability of accumulating Na + and Cl − in their tissue when the species were exposed to the simulated greenhouse effluent [12].…”
Section: Introductionmentioning
confidence: 99%